Optimal bank transparency - Diego Moreno; Tuomas Takalo (Bank of Finland, 2012)
Consider a competitive bank whose illiquid asset portfolio is funded by short-term debt that needs to be refinanced before the asset matures. In this setting, we show that maximal transparency is not socially optimal, and that the existence of social externalities of bank failures reduces further the optimal level of transparency. Moreover, asset risk taking decreases as the level of transparency decreases towards the socially optimal level. As for the sign of the impact of transparency on refinancing risk, it is negative given the assets risk, but it is ambiguous if we account for its indirect effect via risk taking.
URN:NBN:fi:bof-20140807505
Keywords: 330